2007
DOI: 10.1177/0363546507308939
|View full text |Cite
|
Sign up to set email alerts
|

Development of a National Cruciate Ligament Surgery Registry

Abstract: A national population-based cruciate ligament registry has been developed, implemented, and maintained in Norway. The registry will each year enroll approximately 1500 primary cruciate ligament reconstruction cases. It is expected that inadequate procedures and devices can be identified, as well as prognostic factors associated with good and poor outcomes, at least for the most frequent categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
276
2
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 234 publications
(296 citation statements)
references
References 27 publications
3
276
2
15
Order By: Relevance
“…Established in June 2004, the Norwegian first two years recorded 2714 primary ACL reconstructions. Of these, 77% received prophylactic anticoagulation and 5% encountered perioperative complications, 'most often due to graft failure' [29]. Interestingly the use of thromboprophylaxis ranged from 17% in Denmark to 78% in Norway but no information on type, duration, or dosage was available [30].…”
Section: Discussionmentioning
confidence: 99%
“…Established in June 2004, the Norwegian first two years recorded 2714 primary ACL reconstructions. Of these, 77% received prophylactic anticoagulation and 5% encountered perioperative complications, 'most often due to graft failure' [29]. Interestingly the use of thromboprophylaxis ranged from 17% in Denmark to 78% in Norway but no information on type, duration, or dosage was available [30].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the peak occurred in their mid to late twenties [39][40][41][42][43] with the exception of one recent study [44]. These data suggest that sports exposure is a risk factor for ACL injury.…”
Section: Introductionmentioning
confidence: 84%
“…[7,8,[31][32][33] In 2010, this was a summary of the 10 most commonly asked questions by clients at Astonlee Veterinary Hospital:…”
Section: Client Feedbackmentioning
confidence: 99%